2019
DOI: 10.3892/etm.2019.7440
|View full text |Cite
|
Sign up to set email alerts
|

H2S attenuates sepsis‑induced cardiac dysfunction via a PI3K/Akt‑dependent mechanism

Abstract: The heart is the most vulnerable target organ in sepsis, and it has been previously reported that hydrogen sulfide (H 2 S) has a protective role in heart dysfunction caused by sepsis. Additionally, studies have demonstrated that the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) signaling pathway has a protective function during sepsis. However, the potential association between H 2 S and PI3K/Akt in sepsis-induced cardiac dysfunction is unclear. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
1
21
0
2
Order By: Relevance
“…In many animal models of sepsis, endothelial cell damage is associated with apoptosis [19,40,41]. Additionally, improvement of the PI3K/Akt signaling pathway attenuated apoptosis and improved survival in animal models of sepsis [41][42][43]. ADSCs and exosomes have the potential to trigger the PI3K/Akt signaling pathway in wound healing [44] and myocardial ischemia/reperfusion injury [45].…”
Section: Discussionmentioning
confidence: 99%
“…In many animal models of sepsis, endothelial cell damage is associated with apoptosis [19,40,41]. Additionally, improvement of the PI3K/Akt signaling pathway attenuated apoptosis and improved survival in animal models of sepsis [41][42][43]. ADSCs and exosomes have the potential to trigger the PI3K/Akt signaling pathway in wound healing [44] and myocardial ischemia/reperfusion injury [45].…”
Section: Discussionmentioning
confidence: 99%
“…In many sepsis animal models, endothelial cell damage is associated with apoptosis [19,40,41]. Additionally, improvement of the PI3K/Akt signaling pathway attenuated apoptosis and improved survival in sepsis animal models [41][42][43]. ADSCs and exosomes have the potential to trigger the PI3K/Akt signaling pathway in wound healing [44] and myocardial ischemia/reperfusion injury [45].…”
Section: Discussionmentioning
confidence: 99%
“… 9 Interestingly, the PI3K/Akt pathway contributes to HI-induced brain damage through suppressing microglial activation, neuroinflammation and neuronal apoptosis. 10 In addition, the protective effects of H 2 S treatment in myocardial 11 and cerebral ischemia were positively associated with this PI3K/Akt signaling pathway. 12 Based on these findings, we found that stimulation of Akt phosphorylation by L-Cysteine rescues brain function in neonatal mice exposed to HI insult.…”
Section: Introductionmentioning
confidence: 96%